2017
DOI: 10.1155/2017/1796145
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics in Patients with Triple Negative Breast Cancer

Abstract: Purpose The purpose of this study was to compare and contrast the clinical characteristics of the triple negative breast cancer (TNBC) and non-TNBC patients, with a particular focus on genetic susceptibility and risk factors prior to diagnosis. Methods Our institutional database was queried for all patients diagnosed with invasive breast cancer between January 2010 and May 2016. Results Out of a total of 1964 patients, 190 (10%) patients had TNBC. The median age for both TNBC and non-TNBC was 59 years. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 38 publications
(44 reference statements)
2
23
0
1
Order By: Relevance
“…is may be considered as younger age and is comparable to other Indian studies [4,6]. In contrast to this, older age at diagnosis was observed in Western studies [16,17]. is shows that TNBC is affecting young Indian population [18] and most probably reflects the general tendency of breast cancers occurring a decade earlier.…”
Section: Journal Of Oncologysupporting
confidence: 75%
“…is may be considered as younger age and is comparable to other Indian studies [4,6]. In contrast to this, older age at diagnosis was observed in Western studies [16,17]. is shows that TNBC is affecting young Indian population [18] and most probably reflects the general tendency of breast cancers occurring a decade earlier.…”
Section: Journal Of Oncologysupporting
confidence: 75%
“…Triple-negative breast cancer (TNBC) is considered to be one of the most aggressive subtypes of BCa based on its clinical characteristics, including increased proliferative rate, high metastatic potential, and shorter survival outcomes (overall and relapse-free) [ 1 – 5 ]. It accounts for 15-20% of all diagnosed BCa cases [ 6 – 8 ] and has an increased prevalence in African American and Asian women (~30%–65%) compared to other ethnicities [ 9 – 16 ]. TNBC is defined by the lack in expression of the common BCa markers, estrogen receptor (ER), progesterone receptor (PR), and epidermal growth factor receptor 2/HER2/neu (HER2) [ 17 ], which classify other types of BCa and serve as targets for specific treatments; thus, development of targeted therapies for TNBC has been severely hampered.…”
Section: Introductionmentioning
confidence: 99%
“…15 Another institutional database study in US including patients diagnosed with invasive breast carcinoma found higher proportion of TNBC cases (12%) than non-TNBC (9%) among Asian population. 16 On the contrary, a cohort study comprising four ethnic groups-African, American, Hispanic and Asian women found that Asian women were at the lowest risk for TNBC occurrence compared to all three other groups. 17 However, TNBC studies in Asian or, South Asian region reported a moderate to high proportion of TNBC patients among all breast cancer subtypes ranging from (15-25) % in most cases.…”
Section: Tnbc Prevalence In Bangladeshmentioning
confidence: 97%
“…It has been reported that TNBC patients are the most common carriers of BRCA1 mutation among all breast cancer subtypes. 16 A study evaluating the BRCA mutation among different ethnic groups in a genetic counselling cohort reported 139 (30.8%) of total 469 TNBC patients confirming BRCA mutation where 106 of them had BRCA1 and 32 of them had BRCA2 mutation. BRCA mutation data according to race and age was also reported in the same study.…”
Section: Tnbc Risk Factors For Bangladeshi Womenmentioning
confidence: 99%